Genotype × environment interaction of lowland bread wheat varieties for irrigation in different areas of Oromia. Issue 1 (2nd January 2023) - Bayissa, Tilahun; Mengistu, Girma; Gerema, Geleta; Balcha, Urgaya; Feyisa, Hailu; Kedir, Aliyi; Legese, Zeleke; Asegid, Desu; Leta, Tesfaye; Jobe, Tafa
Abstract: Ethiopia is the leading wheat producer in Sub‐Saharan Africa, and the productivity has increased in the last few years. There is also a potential for irrigated wheat production in the lowlands, even though its cultivation is at infant stage. The experiment was conducted in the Oromia region at nine locations in 2021 with irrigation. The study aimed to select high yielding and stable bread wheat variety/ies for lowland areas. Twelve released bread wheat varieties were tested using randomized complete block design with two replications. Environment had the largest effect, 76.5% of total variability, while genotypes 5.0% and GE interaction 18.5% explained total sum of squares. The average grain yield of varieties across locations ranged from the lowest 1.40 t ha −1 at Girja to the highest 6.55 t ha −1 at Daro Labu, with a grand mean of 3.14 t ha −1 . The result showed that varieties released for irrigated areas, Fentale 1, Ardi, and Fentale 2, were ranked the top three based on overall environment mean grain yield. The first and second principal component account 45.5% and 24.7% of the genotype by environment interaction (G × E), respectively, explained 70.2% of the total variation. Daro Lebu and Bedeno were the most productive environment, while Girja was the least productive of irrigated bread wheat for lowlands of the Oromia region. Genotype Selection Index (GSI) showed that varieties Fentale 2, Fentale 1, Pavon 76, and ETBW9578 are stable and high yielding. Based on AMMI and GGE biplot analysis, Girja indicated the most discriminating area and Sewena as representative environment for selecting wide adaptable irrigated lowland varieties. The results of the present study indicated that Fentale 2 and Fentale 1 showed better yield stability across all test environments, therefore, these bread wheat varieties are recommended for wide cultivation in irrigated areas of the Oromia region. Abstract : Twelve bread wheat varieties were evaluated in nine locations. The highest grain yield of 6.55 t ha −1 was obtained during variety testing. Fentale 2 and Fentale 1 varieties gave better yield stability across all locations were recommended.